Emergence and N metabolism of Canavalia ensiformis (L.) DC. seedlings in soil contaminated by nickel - Raqueti, Gabriela S. [UNESP]; Ferreira, Tassia Caroline [UNESP]; Olivio, Maiara Luzia G. [UNESP]; Morais, Fábio A.A. [UNESP]; Coscione, Aline Renee; Camargos, Liliane S. [UNESP] (University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca, 2025)
Heavy metals such as nickel (Ni) can lead to bioaccumulation, affecting entire ecosystems and posing significant risks to various life forms, including plants. Although Ni is a micronutrient, it can be toxic by impacting enzyme activities and inhibiting seed germination and plant growth. In Brazil, official guidelines stipulate preventive and intervention values for Ni concentrations in soil to mitigate pollution and protect soil and groundwater quality. Soil samples classified as Typic Haplustox were artificially contaminated with NiCl2 at concentrations of 120 (T120), 240 (T240), and 360 (T360) mg dm-3, alongside a control treatment (T0). Seeds were cultivated under greenhouse conditions, and germination and growth parameters were analyzed after 15 days. Measurements included emergence speed index, germination percentage, root and shoot length, fresh and dry mass, and biochemical analyses of nitrogenous compounds and sugars. This study addresses the effects of toxic concentrations of NiCl2 on plants, focusing on the germination and early growth stages. Canavalia ensiformis (L.) DC., a tropical legume with significant roles in green manure and phytoremediation, was chosen for its adaptability to various soils. The hypothesis is that C. ensiformis can withstand high soil Ni concentrations, maintaining growth despite environmental toxicity limits. The results indicated differential impacts of Ni, the emergence percentage decreases at 360 mg dm-3 soil with greater dry mass accumulation at 120 and 240 mg dm-3, highlighting the importance of understanding plant responses to stress from potentially toxic elements for sustainable agricultural practices and environmental management.
Keywords: Fabaceae; germination; heavy metal; metabolism; micronutrient; potentially toxic element